GASEOUS TRANSPORT AND DEPOSITION OF GOLD IN MAGMATIC FLUID: EVIDENCE FROM THE ACTIVE KUDRYAVY VOLCANO, KURILE ISLANDS - Yudovskaya M.A.; Distler V.V.; Chaplygin I.V.; Mokhov A.V.; Trubkin N.V.; Gorbacheva S.A. (My University, 2006)
The distribution of gold in high-temperature fumarole gases of the Kudryavy volcano (Kurile Islands) was measured for gas, gas condensate, natural fumarolic sublimates, and precipitates in silica tubes from vents with outlet temperatures ranging from 380 to 870°C. Gold abundance in condensates ranges from 0.3 to 2.4 ppb, which is significantly lower than the abundances of transition metals. Gold contents in zoned precipitates from silica tubes increase gradually with a decrease in temperature to a maximum of 8 ppm in the oxychloride zone at a temperature of approximately 300°C. Total Au content in moderate-temperature sulfide and oxychloride zones is mainly a result of Au inclusions in the abundant Fe-Cu and Zn sulfide minerals as determined by instrumental neutron activation analysis. Most Au occurs as a Cu-Au-Ag triple alloy. Single grains of native gold and binary Au-Ag alloys were also identified among sublimates, but aggregates and crystals of Cu-Au-Ag alloy were found in all fumarolic fields, both in silica tube precipitates and in natural fumarolic crusts. Although the Au triple alloy is homogeneous on the scale of microns and has a composition close to (Cu,Ni,Zn)3(Au,Ag)2, transmission electron microscopy (TEM) shows that these alloy solid solutions consist of monocrystal domains of Au-Ag, Au-Cu, and possibly Cu2O. Gold occurs in oxide assemblages due to the decomposition of its halogenide complexes under high-temperature conditions (650-870°C). In lower temperature zones (<650°C), Au behavior is related to sulfur compounds whose evolution is strongly controlled by redox state. Other minerals that formed from gas transport and precipitation at Kudryavy volcano include garnet, aegirine, diopside, magnetite, anhydrite, molybdenite, multivalent molybdenum oxides (molybdite, tugarinovite, and ilsemannite), powellite, scheelite, wolframite, Na-K chlorides, pyrrhotite, wurtzite, greenockite, pyrite, galena, cubanite, rare native metals (including Fe, Cr, Mo, Sn, Ag, and Al), Cu-Zn-Fe-In sulfides, In-bearing Pb-Bi sulfosalts, cannizzarite, rheniite, cadmoindite, and kudriavite. Although most of these minerals are fine-grained, they are strongly idiomorphic with textures such as gas channels and lamellar, banded, skeletal, and dendrite-like crystals, characteristic of precipitation from a gas phase. The identified textures and mineral assemblages at Kudryavy volcano can be used to interpret geochemical origins of both ancient and modern ore deposits, particularly gold-rich porphyry and related epithermal systems. © Springer-Verlag 2006.
Keywords: CU-AU-AG ALLOY; GAS TRANSPORT; GOLD; KUDRYAVY VOLCANO